2020
DOI: 10.1080/07315724.2020.1770636
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Milk-Substitution Enhance Body Composition and Bone Health in Adolescent Girls

Abstract: Background: Increased soft-drink consumption has contributed to poor calcium intake with 90% of adolescent girls consuming less than the RDA for calcium. Purpose/objectives: The purpose of this investigation was to determine the independent and additive effects of two interventions (milk and resistance training) on nutrient adequacy, body composition, and bone health in adolescent girls. Methods: The experimental design consisted of four experimental groups of adolescent girls 14-17 years of age:A few signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Milk is considered beneficial for child growth and development as it is an excellent source of essential nutrients ( 18 ). Previous studies showed that milk intake might reduce the risk of chronic diseases such as overweight and obesity ( 19 ), metabolic syndrome ( 20 ), high-blood pressure ( 21 ), as well as improve bone health ( 22 ) and sleep satisfaction ( 23 ). A few studies showed that compared to TD children, children with ASD aged 4–10 years have less frequent milk intake ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Milk is considered beneficial for child growth and development as it is an excellent source of essential nutrients ( 18 ). Previous studies showed that milk intake might reduce the risk of chronic diseases such as overweight and obesity ( 19 ), metabolic syndrome ( 20 ), high-blood pressure ( 21 ), as well as improve bone health ( 22 ) and sleep satisfaction ( 23 ). A few studies showed that compared to TD children, children with ASD aged 4–10 years have less frequent milk intake ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with a higher level of physical activity present better ASMI and lower body fat percentage than those with lower levels of physical activity ( 60 ). Hence, physical activity enhances the development, growth, and quality of bone tissue by biomechanical traction when the muscle is subjected to external loads such as resistance training reported in children, adolescents, and adults ( 61 , 62 ). For instance, myostatin (i.e., myokine produced and released by myocytes that acts on muscle cells to inhibit muscle growth) is regulated by physical activity and, in both animal and human studies, reduces its expression and increases bone turnover, leading to an increase in total bone mass ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…This concern may be even more critical in overweight/obese girls because they displayed higher intramuscular fat (lower muscle density) and low lean mass than their normal-weight lean peers ( 67 ). Thereby, increasing ASMI through physical activity (i.e., resistance training) would help to increase bone quality through fat reduction ( 62 , 68 , 69 ). This suggestion has practical applicability, as a meta-analysis ( 70 ) that evaluated the effect of interventions with high-intensity physical exercise and sports mini-games at school showed that girls are more responsive to increasing bone mineral density than boys.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as competition for nutrients between mother and fetus in pregnancies occurs when mothers are still growing, pregnancy may limit maternal growth [7,23,24]. Many adolescents have poor diet quality and poor knowledge of appropriate nutrition; these habits may not change during pregnancy as reduce ingestion of milk and dairy products, and increased soft drinks consumption which has contributed to poor calcium intake [4,25,26].…”
Section: Adolescent Growthmentioning
confidence: 99%